The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1519-69842013000400027
|View full text |Cite
|
Sign up to set email alerts
|

Size and shape in Melipona quadrifasciata anthidioides Lepeletier, 1836 (Hymenoptera; Meliponini)

Abstract: This study aimed to identify differences in wing shape among populations of Melipona quadrifasciata anthidioides obtained in 23 locations in the semi-arid region of Bahia state (Brazil). Analysis of the Procrustes distances among mean wing shapes indicated that population structure did not determine shape variation. Instead, populations were structured geographically according to wing size. The Partial Mantel Test between morphometric (shape and size) distance matrices and altitude, taking geographic distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…reduced genetic variation). Moreover, previous reports have shown that fore wing size and shape of some Melipona species are influenced by both geographic distance and altitude, like that observed in M. scutellaris Latreille (Nunes et al 2007), M. quadrifasciata anthidioides Lepeletier (Nunes et al 2013) and M. subnitida Duke (Lima et al 2014). Nonetheless, no significant morphometric differences were observed in M. mandacaia in relation to altitude (p>0.05), but both fore wing size and shape were correlated to geographic distance (p<0.001 and p<0.05, respectively).…”
Section: Discussionmentioning
confidence: 73%
“…reduced genetic variation). Moreover, previous reports have shown that fore wing size and shape of some Melipona species are influenced by both geographic distance and altitude, like that observed in M. scutellaris Latreille (Nunes et al 2007), M. quadrifasciata anthidioides Lepeletier (Nunes et al 2013) and M. subnitida Duke (Lima et al 2014). Nonetheless, no significant morphometric differences were observed in M. mandacaia in relation to altitude (p>0.05), but both fore wing size and shape were correlated to geographic distance (p<0.001 and p<0.05, respectively).…”
Section: Discussionmentioning
confidence: 73%
“…Studies on population structure and geographic variation of bees have been carried out based on morphometric data comparing races or populations (Ferreira et al, 2011;Lima Junior et al, 2012;Nunes et al, 2013). Those analyses are usually based on wing characters due to their high heritability and because they are strongly affected by the environment (Diniz-Filho & Bini, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we extracted 12 landmarks from the FW of six Plebeia species. Nevertheless, historically, entomologists have obtained seven to 20 LMs from bee wings, depending of bold venation and its capacity to clearly discern as much as possible the homologous anatomical marks (Aytekin et al, 2007;Combey et al, 2013;Nunes et al, 2013;Falamarzi et al, 2016;Francoy et al, 2016;Prado-Silva et al, 2018). Further, other insect structures, such as genitalia, mandibles and head, are adequate attributes but are rarely used in GM for evaluating morphological variation in bees (Tatsuta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%